2020
DOI: 10.3390/cells9030616
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal MACF1 Facilitates SMAD7 Nuclear Translocation to Drive Bone Formation

Abstract: Microtubule actin crosslinking factor 1 (MACF1) is a large crosslinker that contributes to cell integrity and cell differentiation. Recent studies show that MACF1 is involved in multiple cellular functions such as neuron development and epidermal migration, and is the molecular basis for many degenerative diseases. MACF1 is highly abundant in bones, especially in mesenchymal stem cells; however, its regulatory role is still less understood in bone formation and degenerative bone diseases. In this study, we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 45 publications
(45 reference statements)
1
21
0
Order By: Relevance
“…Our previous data show that MACF1 positively regulates osteoblast differentiation and bone formation by activating the Wnt/β-catenin or BMP signaling pathways 49 - 52 , which are also likely involved in miR-138 regulation of osteogenic differentiation 47 , 48 . In addition, MACF1, as a cytoskeleton crosslinker, is negatively correlated with age and also mechanoresponsive under different mechanical conditions 49 , 52 - 55 . We also found that the transfection of the Macf1 3'UTR repeated sequence showed effects similar to those of the miR-138-5p inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous data show that MACF1 positively regulates osteoblast differentiation and bone formation by activating the Wnt/β-catenin or BMP signaling pathways 49 - 52 , which are also likely involved in miR-138 regulation of osteogenic differentiation 47 , 48 . In addition, MACF1, as a cytoskeleton crosslinker, is negatively correlated with age and also mechanoresponsive under different mechanical conditions 49 , 52 - 55 . We also found that the transfection of the Macf1 3'UTR repeated sequence showed effects similar to those of the miR-138-5p inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Microtubule actin crosslinking factor 1 (MACF1), a spectraplakin protein that interacts with the cytoskeleton, plays an important role in cell migration 10 - 13 . We previously found that Macf1 was significantly downregulated in aged osteoporotic patients 14 . In the current study, we identified a long non-coding RNA PMIF (postulated migration inhibitory factor, i.e.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, down‐regulated Smad ubiquitination regulatory factor 1 (SMURF1) is found to promote the expression of SMAD7 in mesangial cells 12,13 . SMAD7 is promoted by the interaction between microtubule actin crosslinking factor 1 and SMAD7 to accelerate the osteogenesis 14 . Furthermore, up‐regulated SMAD7 is closely related to the proliferation of BMSCs 15 .…”
Section: Introductionmentioning
confidence: 99%